2003
DOI: 10.1097/01.brs.0000103341.45133.f3
|View full text |Cite
|
Sign up to set email alerts
|

Human Nucleus Pulposis Can Respond to a Pro-inflammatory Stimulus

Abstract: We conclude that both scoliotic and degenerate human nucleus pulposus can respond to an exogenous pro-inflammatory stimulus by secreting increased amounts of IL-6, IL-8, and PGE2 but not TNF-alpha and that degenerate disc tissue is more sensitive to a pro-inflammatory stimulus than its scoliotic counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 42 publications
3
82
0
Order By: Relevance
“…The presence of TNF␣ in herniated disc tissue has long been controversial; while some studies have shown TNF␣ in herniated disc tissue (8,15), others have shown opposite findings (9,10,12,14). Our results indicate that TNF␣ appears transiently in the relatively early stage of IVD-macrophage interaction, suggesting that TNF␣ expression might vary at different stages of herniated disc disease.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The presence of TNF␣ in herniated disc tissue has long been controversial; while some studies have shown TNF␣ in herniated disc tissue (8,15), others have shown opposite findings (9,10,12,14). Our results indicate that TNF␣ appears transiently in the relatively early stage of IVD-macrophage interaction, suggesting that TNF␣ expression might vary at different stages of herniated disc disease.…”
Section: Discussionmentioning
confidence: 48%
“…TNF␣ is always present in the nucleus pulposus and is thought to induce painrelated behavior in animal models (21,22). High levels of IL-6, IL-8, and PGE 2 are produced in human herniated disc tissue (9,10,12,13,15,19), and their levels show significant correlations with preoperative symptoms of herniated disc disease (8,10,17). However, the mechanisms by which TNF␣, IL-6, IL-8, and PGE 2 contribute to herniated disc disease symptoms, especially sciatica, are unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Le Maitre et al [21] reported that TNF-a and IL-1b are expressed by cells in degenerate intervertebral disc tissues and may be associated with pathogenesis of intervertebral disc degeneration. However, Burke et al [8] found that there is no TNF-a or IL1b secretion by intervertebral disc tissues after stimulation with lipopolysaccharide. We found that IL-6, IL-8, and PGE2 are increased after stimulation with MIF, although TNF-a and IL-1b do not increase.…”
Section: Discussionmentioning
confidence: 99%
“…(166,167) The latest therapeutic strategies for DD have included some efforts in upregulating the production of key matrix proteins (e.g., aggrecan), or downregulating the catabolic events induced by the proinflammatory cytokines, IL-1 and TNF-a. (109,(168)(169)(170)(171)(172)(173)(174) To deliver these therapeutic agents, some approaches such as protein injection and viral or non-viral gene transfer have been suggested and preclinically tested. (167,(175)(176)(177) The most direct approach to regenerate or repair a degenerated IVD is by injecting anabolic factors.…”
Section: Lbp Pathophysiologymentioning
confidence: 99%